2022
DOI: 10.3389/fcell.2022.1005926
|View full text |Cite
|
Sign up to set email alerts
|

MSCs vs. iPSCs: Potential in therapeutic applications

Abstract: Over the past 2 decades, mesenchymal stem cells (MSCs) have attracted a lot of interest as a unique therapeutic approach for a variety of diseases. MSCs are capable of self-renewal and multilineage differentiation capacity, immunomodulatory, and anti-inflammatory properties allowing it to play a role in regenerative medicine. Furthermore, MSCs are low in tumorigenicity and immune privileged, which permits the use of allogeneic MSCs for therapies that eliminate the need to collect MSCs directly from patients. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 218 publications
0
21
0
Order By: Relevance
“…1 The multilineage differentiation potential of the induced MSCs further highlights their suitability for therapeutic applications in treating various diseases and injuries. 29,30 Notably, we observed that the differentiated MSCs from both ESCs and iPSCs expressed low levels of hematopoietic markers, such as CD14, CD19, CD34, and CD45. 31 This finding suggests that the induced MSCs have a low potential to differentiate into hematopoietic lineage.…”
Section: Discussionmentioning
confidence: 92%
“…1 The multilineage differentiation potential of the induced MSCs further highlights their suitability for therapeutic applications in treating various diseases and injuries. 29,30 Notably, we observed that the differentiated MSCs from both ESCs and iPSCs expressed low levels of hematopoietic markers, such as CD14, CD19, CD34, and CD45. 31 This finding suggests that the induced MSCs have a low potential to differentiate into hematopoietic lineage.…”
Section: Discussionmentioning
confidence: 92%
“…The laminin promoted an increase in neuronal differentiation and an increase in the number of neurospheres with migrated neurons . However, the use of iPSCs imposes the threat of mutations and increased probability of teratoma formation as compared to mesenchymal stem cells. CNS-derived neural stem cells and oligodendrocytes combined with an alginate-based scaffold markedly promoted nerve regeneration after spinal cord injury .…”
Section: Discussionmentioning
confidence: 99%
“…Lentiviruses have a higher cloning capacity and higher infection efficiency than retroviruses. Unlike MMLV, lentiviruses can replicate in dividing and non-dividing cells ( Thanaskody et al, 2022 ). Both lentiviruses and retroviral vectors carry a high risk of insertion mutation during transfection because of their genomic integration.…”
Section: Biological Vectorsmentioning
confidence: 99%